Identification of a novel mutation in the OsMRP5 gene in low phytate Basmati rice mutant and development of CAPS marker for marker-assisted breeding - Qamar, Zia-ul-; Uzair, Muhammad; Hameed, Amjad; Zafar, Syed Adeel; Li, Xueyong (Frontiers in Plant Science, 2024)
Low phytate level is a desirable trait because it promotes mineral bioavailability and thus offers a solution to tackle mineral deficiencies. The objectives of the present study were to characterize low phytate (lpa) Basmati rice mutants for the identification of novel mutations in target gene(s) and to develop a PCR-based CAPS (cleaved amplified polymorphic sequence) marker for low phytate Basmati rice. For this purpose, cultivar Super Basmati (Q4) was irradiated with gamma rays ( 60 Co source) and three mutants named Q1 (lpa-5-9), Q2 (lpa-9-13), and Q3 (lpa-59-14) were isolated. Four genes previously been reported for the low phytic acid trait in rice were sequenced in these mutants and no mutation was observed in Q1 and Q2. However, in Q3 (lpa14) mutant a novel mutation in OsMRP5 gene (LOC_Os03g04920`) was detected. Sequence analysis displayed a substitution in the first exon of OsMRP5 at position 1142 bp resulting in the amino acid change from glycine (Gly) to alanine (Ala) at position 381a.a. To facilitate low-phytate breeding program, CAPS marker was developed to confirm this mutation site using the restriction digestion by AluI restriction enzyme. After enzyme digestion, Q3 produces four bands (32, 220, 154, and 32 bp) while Q4 (parent cultivar Super Basmati) produces only 3 bands (32, 374, and 32 bp). These results showed that this CAPS marker is 100% linked with this mutation and can be used for future breeding programs. Present findings provided insights in molecular basis of low phytate trait in rice paving the way for developing low-phytate rice varieties through marker-assisted breeding.